Comparison of the virtual reality and mobile games regarding physiological load - Biçer, Bilal; Löklüoğlu, Berkay (Frontiers in Physiology, 2025)
IntroductionPhysical inactivity or lack of physical activity has become an increasingly widespread and important global public health problem. Along with technological developments, the interest in e-sports is also increasing. Virtual reality (VR) games applied within the scope of e-sports include physical movements by nature, which encourages players to move more and be active. This study aimed to compare VR and mobile games regarding physiologic load.MethodsTwenty-two (13 males, 9 females) healthy university students with a mean age of 21.72 ± 1.39 years, height of 171.59 ± 9.12 cm, and body weight of 64.95 ± 13.35 kg, who did not smoke, did not play sports professionally, and did not have chronic diseases, voluntarily participated in the study. Participants were randomly assigned to play an active video game (VR) using a virtual reality headset and a mobile game (MO) on a smartphone for 2 days. The game duration was determined as 15 min. The body temperature of the participants before and after the game and heart rate (HR) values during the game were measured from beat to beat. A non-contact infrared thermometer was used for measuring body temperature, and a telemetric device was used for HR measurements.ResultsWhen VR and MO games were compared regarding body temperature, no intra- and inter-group differences were observed. Regarding HR, HRmean, HRmax, and HRtotal values of the VR game were statistically significantly higher than MO games. In addition, in the analyses performed according to the time spent in the percentage of maximal heart rate, it was observed that the time spent in the MO game was significantly longer compared to the VR game below the Under Very Light (UVL). On the contrary, the time spent in the VR game was significantly longer than the MO game at Above Very Light (AVL).ConclusionAs a result, the heart rate parameters measured in the VR game were higher than in the MO game at all levels, suggesting that VR may be an effective tool for physical activity-based gaming experiences.